SARS-CoV-2 infection in farmed minks, the Netherlands, April and May 2020 - Oreshkova, Nadia; Molenaar, Robert Jan; Vreman, Sandra; Harders, Frank; Oude Munnink, Bas B; Hakze-van der Honing, Renate W; Gerhards, Nora; Tolsma, Paulien; Bouwstra, Ruth; Sikkema, Reina S; Tacken, Mirriam GJ; de Rooij, Myrna MT; et al. (Euro surveillance : bulletin européen sur les maladies transmissibles, 2020)
Respiratory disease and increased mortality occurred in minks on two farms in the Netherlands, with interstitial pneumonia and SARS-CoV-2 RNA in organ and swab samples. On both farms, at least one worker had coronavirus disease-associated symptoms before the outbreak. Variations in mink-derived viral genomes showed between-mink transmission and no infection link between the farms. Inhalable dust contained viral RNA, indicating possible exposure of workers. One worker is assumed to have attracted the virus from mink.